γ-Glutamyltransferase, but not markers of hepatic fibrosis, is associated with cardiovascular disease in older people with type 2 diabetes mellitus: the Edinburgh Type 2 Diabetes Study - Morling, Joanne R.; Fallowfield, Jonathan A.; Williamson, Rachel M.; Robertson, Christine M.; Glancy, Stephen; Guha, Indra Neil; Strachan, Mark W.J.; Price, Jackie F. (Springer, 2015)
AIMS/HYPOTHESIS: We examined the association of prevalent and incident cardiovascular disease (CVD) with chronic liver disease in a cohort of community-based people with type 2 diabetes, in order to clarify the relationship between these two important conditions.